Magnets - Parker, Steve (Milwaukee, Wis. : Gareth Stevens Pub., 1998)
Describes different kinds of magnets and how they are used and presents a variety of experiments and other activities involving magnetism.
Originally published: New York, NY : Lorenz Books, 1997.
"Additional end matter"--T.p. verso.
Includes bibliographical references (p. 66) and index.
Keywords: Magnets -- Juvenile literature; Magnets -- Experiments -- Juvenile literature; Magnetism -- Juvenile literature; Magnets; Magnetism; Magnets -- Experiments; Magnetism -- Experiments; Experiments